2013
DOI: 10.4103/0971-9784.109737
|View full text |Cite
|
Sign up to set email alerts
|

Effect of levosimendan on hemodynamic changes in patients undergoing off-pump coronary artery bypass grafting: A randomized controlled study

Abstract: Levosimendan significantly increased CI and decreased SVRI after OPCAB but it did not show any outcome benefit in terms of duration of ventilation and intensive care unit stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Additionally, Treskatsch et al [ 18 ] and Qiang et al [ 9 ] reported that the levosimendan group experienced shorter durations of ICU stay and mechanical ventilation. However, Kodalli et al [ 19 ], in their double-blind, randomized study involving 30 patients, failed to identify significant differences in ventilation duration and ICU stay. Overall, the accumulated evidence underscores the potential benefits of levosimendan in improving postoperative lung function and reducing ICU-related interventions, although further research is warranted to fully elucidate its impact in diverse clinical contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Treskatsch et al [ 18 ] and Qiang et al [ 9 ] reported that the levosimendan group experienced shorter durations of ICU stay and mechanical ventilation. However, Kodalli et al [ 19 ], in their double-blind, randomized study involving 30 patients, failed to identify significant differences in ventilation duration and ICU stay. Overall, the accumulated evidence underscores the potential benefits of levosimendan in improving postoperative lung function and reducing ICU-related interventions, although further research is warranted to fully elucidate its impact in diverse clinical contexts.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, systemic vascular resistance index during the weaning from CPB was lower in both groups and epinephrine group showed a lower systemic vascular resistance index when compared to levosimendan group in the post-CPB period. Inodilation action of levosimendan can frequently lead to reduction in systemic vascular resistance by phosphodiesterase type III inhibition, open ATP-sensitive K + channels and nitric oxide release [ 2 , 26 , 26 , 40 ]. In the present study, even with optimal loading conditions, to avoid systemic arterial hypotension we used a continuous infusion of norepinephrine when mean arterial pressure remained below 60 mmHg; thus, levosimendan group required more norepinephrine than epinephrine group (epinephrine group: 16% vs. levosimendan group: 47%; p = 0.001) [ 2 , 5 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inodilation action of levosimendan can frequently lead to reduction in systemic vascular resistance by phosphodiesterase type III inhibition, open ATP-sensitive K + channels and nitric oxide release [ 2 , 26 , 26 , 40 ]. In the present study, even with optimal loading conditions, to avoid systemic arterial hypotension we used a continuous infusion of norepinephrine when mean arterial pressure remained below 60 mmHg; thus, levosimendan group required more norepinephrine than epinephrine group (epinephrine group: 16% vs. levosimendan group: 47%; p = 0.001) [ 2 , 5 , 40 ]. Therefore, increase in systemic vascular resistance index in levosimendan group compared with epinephrine group at post-CPB period might have been caused by the higher amount of norepinephrine administered in levosimendan group.…”
Section: Discussionmentioning
confidence: 99%